Prehospital analgesia for trauma-related pain by paramedics: a comparative retrospective observational study of paracetamol, nalbuphine plus paracetamol, and piritramide - Lohmann, Jonas; Deicke, Martin; Deslandes, Marvin; Grannemann, Julia Johanna; Kolaparambil Varghese, Lydia Johnson; Hinkelbein, Jochen; Hoyer, Annika; Kalmbach, Matthias; Plappert, Thomas; Strickmann, Bernd; Vaseekaran, Mathini; Vollmer, Tobias; et al. (Scandinavian journal of trauma, resuscitation and emergency medicine, 2025)
Background In this retrospective observational study, we compared the efficacy and safety of paracetamol compared with those of nalbuphine plus paracetamol and piritramide in prehospital analgesia for trauma-related pain administered by paramedics. Methods All prehospital analgesia for trauma-related pain administered by paramedics in the emergency medical services of the districts of Fulda (piritramide) and Guetersloh (paracetamol, nalbuphine plus paracetamol) was analyzed based on electronic medical records. Primary endpoint was effective analgesia defined as a numeric rating scale (NRS) score ≤ 4 at hospital admission. Safety was evaluated based on the occurrence of drug-related complications (nausea/vomiting, antiemetic use, reduced level of consciousness, respiratory or hemodynamic insufficiency). Results A total of 1,295 interventions (district of Guetersloh: n = 784 [60.5%], district of Fulda: n = 511 [39.5%]) were analyzed. Paracetamol: n = 291 [22.5%], initial NRS: 6.8 ± 1.4, final NRS: 4.0 ± 1.9. Nalbuphine plus paracetamol: n = 493 [38.1%], initial NRS: 8.2 ± 1.3, final NRS: 3.6 ± 1.9. Piritramide: n = 511 [39.5%], initial NRS: 8.3 ± 1.1, final NRS: 4.3 ± 1.5. The likelihood of achieving NRS ≤ 4 at hospital admission was highest in the nalbuphine plus paracetamol group (odds ratio (OR): 3.25, 95% confidence interval (95% CI): 2.46–4.30) and lower in the piritramide (OR: 0.31, 95% CI: 0.23–0.41) and paracetamol (OR: 0.32, 95% CI: 0.23–0.45) groups. The comparison between piritramide ( n = 30 [5.9%]) and nalbuphine plus paracetamol ( n = 34 [7.7%]) did not reveal evidence for differences in the occurrence of drug-related complications (OR: 0.75, 95% CI: 0.45–1.24). Conclusions Analgesia with nalbuphine plus paracetamol for trauma patients administered by paramedics were more effective in reducing pain to NRS ≤ 4 at hospital admission compared to monotherapy with paracetamol or piritramide, with a comparable safety profile.